2022
DOI: 10.1002/pen.26178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross‐linking on the mechanical properties, degree of crystallinity and thermal stability of polyethylene vitrimers

Abstract: Maleic anhydride‐grafted‐polyethylene was dynamically cross‐linked via reactive melt blending with 4,4′‐dithiodianiline. Thermal and mechanical properties of polyethylene vitrimers with different cross‐linking density were investigated. The results indicate that the degree of crystallinity decreased with increasing cross‐linking density. This behavior was directly related to short‐term and long‐term mechanical properties: vitrimers showed a decrease in yield strength and creep performance. The yield strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…For all samples, HDPE exhibited higher E′ compared to HDPE-V. Previous research has demonstrated a linear relationship between crystallinity and stiffness [ 35 ]. Higher crystallinity in HDPE explains its higher modulus compared to HDPE-V. HDPE samples tested in the 0° orientation showed a drop of approximately 100 MPa in E′ relative to compression-molded HDPE, while the 90° orientation showed a drop of around 300 MPa.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…For all samples, HDPE exhibited higher E′ compared to HDPE-V. Previous research has demonstrated a linear relationship between crystallinity and stiffness [ 35 ]. Higher crystallinity in HDPE explains its higher modulus compared to HDPE-V. HDPE samples tested in the 0° orientation showed a drop of approximately 100 MPa in E′ relative to compression-molded HDPE, while the 90° orientation showed a drop of around 300 MPa.…”
Section: Resultsmentioning
confidence: 85%
“…HDPE-V was obtained from the reaction of HDPE-MAH and the diamine crosslinker containing disulfide bonds—4,4′ dithiodianiline (DTA)—as described in a previous work [ 35 ]. The concentration of MAH was 0.3% wt., and a molar ratio of 1:0.5 (MAH:DTA) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the cross-linking density of PCG- X s increases as the content of the cross-linker (PEG-NH 3 ) increases, the glass-transition temperature ( T g ) and elastic modulus of PCG- X s also increase as the PEG-NH 3 content increases up to 7.5 wt % (Table ). , However, when the content of PEG-NH 3 increases to 10.0 wt %, the T g and elastic modulus decrease due to the increase in the content of the flexible ethylene oxide units . The strong mechanical strength of the polymer binder can improve the cell performance of the Si anode because it can help maintaining the electrode structure from the Si volume change during the charging/discharging process. , Although the T g value of PCG-7.5 is the highest at 65.8 °C, the difference is less than 4 °C, so it is unlikely to significantly affect the cell performance.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, incorporating DCBs within self-assembled systems offers one way to realize reprocessable high-performance materials. Recent work has shown that incorporating dynamic bonds within crystalline systems is useful to modulate rheological properties, crystallinity, and mechanical properties. , A less explored opportunity, however, is the possibility to exploit bond exchange reactions to modulate pathways of self-assembly. Preliminary work in block copolymer , and semicrystalline , polymers suggests that nano- and mesoscale assembly and morphologyand thus emergent propertiesare altered by DCBs.…”
mentioning
confidence: 99%